Effect of Visual Aids During Surgical Consents on Patient Understanding and Satisfaction. Issue 12 (December 2020) - Wang, Rui; Haviland, Miriam J.; Hacker, Michele R.; Lefevre, Roger
Abstract : Objective: This study aimed to assess whether the use of visual aids to augment the consent process for pelvic floor surgeries affects patient understanding and satisfaction. Methods: We conducted a single-blind, randomized controlled trial. Adults planning robotic sacrocolpopexy or suburethral sling surgeries were eligible. All participants received standard preoperative consent counseling. Participants randomized to the intervention also viewed slides with visual aids that paralleled standard counseling; participants randomized to the control group received only standard counseling. All participants completed surveys after their preoperative visit, the day of surgery, and at their postoperative visit. Each survey contained 12 true-false questions about risks, benefits, and alternatives of surgery, and expectations during recovery. The primary outcome was the percentage of correct true-false questions. We conducted an intention-to-treat analysis. Results: We randomized 32 participants undergoing robotic sacrocolpopexy and 32 undergoing suburethral sling surgeries, yielding 16 in the intervention group and 16 in the control group for each procedure. The intervention and control groups for both surgeries were similar in age, body mass index, race, education, and previous surgery for similar symptoms. Among participants undergoing robotic sacrocolpopexies, median knowledge scores at the preoperative visit were similar between the intervention (92% [interquartile range IQR, 86%–100%]) and control (86% [IQR, 75%–94%]) groups ( P = 0.21). Similar results were seen for participants undergoing suburethral sling procedures in the intervention (83.3% [IQR, 71%–92%]) and control (83% [IQR, 75%–88%]) groups ( P = 0.64). Conclusions: We found that using visual aids during the consent process for patients undergoing robotic sacrocolpopexy or suburethral sling surgeries did not improve knowledge.